Quantitative assessment of palatal bone thickness in an ethnic Indian population: A computed tomography study - Ganesan Jayakumar; Rajkumar; Tom Biju; M Ashwin George; N R Krishnaswamy (Wolters Kluwer Medknow Publications, 2012)
Context: Variations in palatal bone thickness (PBT) at various locations have caused considerable problems when using these sites for anchorage purposes. Aims: To find the comparative thickness of the palatal bone at different locations and to validate its morphology for anchorage purposes using mini-implants (MI). Settings and Design: This investigation was undertaken to compare the mean PBT and level of significance of differences between male and female subjects and between two different age-groups. Materials and Methods: The computed tomography (CT) data for 60 patients (30 males and 30 females) in two different age-groups (group A: 15-24 years; group B: 25-35 years) were imported into CAD-based medical software, (MIMICS® ; Materialise, Belgium) for multiplanar reconstruction. The measurements were made in two planes- transverse and sagittal-and at different positions in each of the planes. Statistical Analysis: The mean and standard deviations of the PBT at different points were calculated. The Student's t-test and Mann-Whitney U test were used for comparisons between the groups. Results: Significant variations were observed in the thickness of the palatal bone for both groups tested, with the anterior region at 4 mm behind the incisive papilla showing the maximum thickness. Conclusions: Despite the palatal bone being thickest in the mid-palatal suture (MPS) region, this is not the ideal site for anchorage purposes due to inadequate calcification and interposition of connective tissue, especially in young growing children. So, the alternate optimum position is the paramedian region, 3 mm lateral to the MPS and 4 mm from the incisive foramen (IF).